The end of the road, no more walking in dead men shoes: IT professionals' experience of being outsourced to the private sector. (1st October 2008) - Simone Dahlmann,
Abstract : This article examines the experiences of IT professional workers in the process of being transferred from local government to private, large multinational IT service providers in the UK. Outsourcing of IT services has become a common practice and often it is the workers' experience of change that is under-captured in research. This article looks at changes in occupational identity, recognition and commitment in the workplace and shows how these factors are perceived by IT professionals in the UK interviewed as part of case study research for a larger, EC-funded research project. The findings point to a clash between the need to adapt to private sector organisational practices and the desire to find meaning in work that has substantially changed.